Monolithic coefficient design values for seismically strengthening RC columns with jackets. Issue 2 (22nd April 2019) - Dritsos, Stephanos; Moseley, Jon
Abstract: Weak structures need to be strengthened. Reinforced concrete is the material of choice used to build structures in many earthquake‐prone regions. In such regions, adding a reinforced concrete jacket to the columns of structures is a traditional and popular strengthening technique. Complex finite element analyses are required to determine the behaviour of strengthened columns and the interface between the new and the old concrete needs to be simulated through the use of specific contact elements. However, to facilitate design in practice, monolithic coefficient values can be applied to an equivalent monolithic column in order to easily estimate the behaviour. In the past, values recommended in seismic codes were either empirical or based on engineering judgment. This paper describes experimental and analytical work carried out at the University of Patras in Greece that resulted in either confirming code values or influenced the latest code specified values. It is concluded that engineers can now have a high degree of confidence in the actual behaviour of strengthened columns during a destructive earthquake, as code specifications are now based on fact.